1984
DOI: 10.1037/0022-0167.31.4.580
|View full text |Cite
|
Sign up to set email alerts
|

Math anxiety: Relation with situational test anxiety, performance, physiological arousal, and math avoidance behavior.

Abstract: The relation of mathematics anxiety to situationally-assessed test anxiety, math performance, physiological arousal, and math avoidance behavior was investigated. Sixty-three undergraduates (23 men, 40 women) completed Suinn's Mathematics Anxiety Rating Scale, Fennema and Sherman's Mathematics Anxiety Scale, Sandman's Anxiety Toward Mathematics Scale, and Spielberger's Test Anxiety Inventory prior to completing three math tasks. During the math tasks, heart rate, skin conductance level, skin fluctuations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 5 publications
10
79
0
4
Order By: Relevance
“…These studies showed parallel results (Garrosa, MorenoJimenez, Liang & González, 2008;Martinussen, Richardsen & Burke, 2007;Suran & Sheridan, 1984). Although some researchers determined that older teachers have higher mathematics anxiety levels than younger teachers (Betz, 1978;Dew, Galassi & Galassi, 1984), some researchers stated that there was a reverse relationship between mathematics anxiety and age and tenure variables (Byrne, 1994;Gold, 1985). In some studies, it is determined that age and tenure variables are not effective in mathematics anxiety (Wiggins, 1984).…”
Section: Introductionmentioning
confidence: 92%
“…These studies showed parallel results (Garrosa, MorenoJimenez, Liang & González, 2008;Martinussen, Richardsen & Burke, 2007;Suran & Sheridan, 1984). Although some researchers determined that older teachers have higher mathematics anxiety levels than younger teachers (Betz, 1978;Dew, Galassi & Galassi, 1984), some researchers stated that there was a reverse relationship between mathematics anxiety and age and tenure variables (Byrne, 1994;Gold, 1985). In some studies, it is determined that age and tenure variables are not effective in mathematics anxiety (Wiggins, 1984).…”
Section: Introductionmentioning
confidence: 92%
“…First, college students have produced significantly reduced MARS scores after receiving treatment for math anxiety (Suinn et aI., 1970;Suinn & Richardson, 1971). Second, scores on the MARS have been found to be significantly, but inversely, related to the performance of college students on a test of mathematical ability (Dew, Galassi, & Galassi, 1984).…”
Section: Outcome Measuresmentioning
confidence: 98%
“…Mathematikangst geht weiterhin mit negativen Einstellungen zu Mathematik, einer geringen Freude an Mathematik und einem niedrigen Selbstbewusstsein in diesem Fach einher (Ashcraft & Kirk, 2001;Hembree, 1990;Krinzinger et al, 2007). Insgesamt ist Mathematikangst trotz der zahlreichen Überschneidungen mit anderen Ängsten und verwandten Variablen dennoch als eigenständiges Konstrukt zu betrachten (Dew, Galassi & Galassi, 1984;Hembree, 1990;Punaro & Reeve, 2012 Ängstlichkeitsausprägung auftreten kann (Rubinsten & Tannock, 2010). Zudem scheint Mathematikangst lediglich schwach mit allgemeiner Intelligenz assoziiert zu sein (Ashcraft, 2002;Maloney & Beilock, 2012).…”
Section: Mathematikangstinterview (Mai)unclassified